2021
DOI: 10.2196/29127
|View full text |Cite|
|
Sign up to set email alerts
|

Content and Dynamics of Websites Shared Over Vaccine-Related Tweets in COVID-19 Conversations: Computational Analysis

Abstract: Background The onset of the COVID-19 pandemic and the consequent “infodemic” increased concerns about Twitter’s role in advancing antivaccination messages, even before a vaccine became available to the public. New computational methods allow for analysis of cross-platform use by tracking links to websites shared over Twitter, which, in turn, can uncover some of the content and dynamics of information sources and agenda-setting processes. Such understanding can advance theory and efforts to reduce m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…In addition, with the rise of TikTok during the COVID-19 pandemic [ 67 ], researchers should consider moving toward building a bridge that connects social media messages related to ACP across platforms and users alike. Finally, future studies may go beyond the text of tweets to examine external links [ 68 ], visual communication [ 69 ], and communication across different social media [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the rise of TikTok during the COVID-19 pandemic [ 67 ], researchers should consider moving toward building a bridge that connects social media messages related to ACP across platforms and users alike. Finally, future studies may go beyond the text of tweets to examine external links [ 68 ], visual communication [ 69 ], and communication across different social media [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis reported here is part of a larger study that examined vaccination-related tweets. 69 The analyzed data were originally collected in two different studies that examined COVID-19 Twitter conversations in the early months of the pandemic. The first data set was based on a collection of tweet IDs gathered using general COVID-19 related keywords, such as “coronavirus” and “Wuhancoronavirus.” 70 We used “hydration,” a a process of gathering all the pertinent information about each tweet into the JavaScript Object Notation (JSON) format file 71 via the Twitter Search API b on all of the tweet IDs.…”
Section: Methodsmentioning
confidence: 99%
“…The use of external links as a method of sharing and spreading information on social media has been much studied (Cruickshank et al 2021;Kümpel et al 2015). This study builds on the past work on social media link sharing behavior to examine the presence of coordinated narrative spread within and across platforms during the January 6th Capitol Riots.…”
Section: Rq3: Are There Similar Narratives That Are Shared Across Pla...mentioning
confidence: 99%
“…Recent research in the field has identified the use of external content like URLs (Horawalavithana et al 2021;Giglietto st al. 2020;Cruickshank et al 2021) and cross-platform behaviors Kin and Sameera 2021;Iamnitchi et al 2020) in the spread of mis/ disinformation.…”
Section: Introductionmentioning
confidence: 99%